CHEMICAL KINETICS AND STABILITY STUDIES OF AMLODIPINE BESYLATE - Kumar, Vinesh; Garg, Shiv; Sharma, Piush (Asian Journal of Pharmaceutical Research and Development, 2018)
The drug Amlodipine besylate was selected to study its chemical kinetics and degradation kinetics under variable conditions such as different temperatures, pH, light, buffers, solvent system and surfactants by applying the principles of chemical kinetics. The solubility of drug was checked in water and different solvents like Dimethyl formamide, methanol, ethanol, propylene glycol, PEG 400, PEG 600 and glycerol. The dug was found to be fully soluble in methanol, DMF, PEG 600, PEG 400, and Propylene glycol. The stock solution was then scanned between 200-400nm and the lmax was found to be 239 nm where the absorbance for 40 mg/ml was 1.1726 (Fig –1). The standard graph of the drug was plotted between concentration and absorbance whish gave a linear plot and the Lambert Beers law was obeyed in the concentration range of 0 to 30mg/ml.